Investigation of the effects of temperature and exposure time on the corrosion behavior of a ferritic steel in CO2 environment using the optimized linear polarization resistance method - Eškinja, Magdalena; Moshtaghi, Masoud; Hönig, Stefan; Zehethofer, Gerald; Mori, Gregor (Results in materials, 2022)
Linear Polarization Resistance was utilized to instantly evaluate the corrosion behavior of a ferritic steel under conditions representative in oilfields (1.5 wt% NaCl solution purged with 1 bar CO2). The effect of input values of corrosion monitoring method with respect to different parameters (time and temperature) of CO2 corrosion has not been elucidated and research about this subject matter cannot be found in the literature. Therefore, scan rate and open circuit potential were optimized, and the validity of the results was confirmed by separate Tafel polarization measurements carried out according to the standards. Long immersion tests and electrochemical measurements were performed to study the effect of time and temperature on CO2 corrosion of the ferritic steel. According to the solubility of iron carbonate (FeCO3) three temperature levels (30 °C, 60 °C, and 90 °C) were studied. The results of cross-sectional observation of the corrosion scale firstly show that a higher temperature (90 °C) leads to a thicker and more protective scale, which consequently yields lower corrosion rates. At a higher temperature, the content of oxygen increases while the content of carbon in a protective layer decreases, which corresponds to the formation of divergent corrosion products at different temperatures. Iron carbonate (FeCO3) was detected as the main component of the layer with highest protective performance.